2003
DOI: 10.1007/s10350-004-6654-6
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Advancement Flap Repair of Rectourethral Fistula

Abstract: The rectal advancement flap provides an effective repair for rectourethral fistula. Successful repair can be achieved in a majority of patients with minimal morbidity, short length of stay, and a good postoperative quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 33 publications
1
49
1
Order By: Relevance
“…However, under direct vision, dissection of the fistula sometimes is extremely difficult or impossible because of severe scar and broad diameter of the fistula [7]. To prevent refistulization, tissue flaps with vascular pedicel, such as omentum, gracilis muscle, or rectal wall have been interposed between the rectum and urethra or vagina [2,3,8], but these procedures were too complex to perform. Moreover, the hypertrophied and dilated colon was difficult to be pulled through the rectum using a posterior sagittal incision alone, such as case 1 and case 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under direct vision, dissection of the fistula sometimes is extremely difficult or impossible because of severe scar and broad diameter of the fistula [7]. To prevent refistulization, tissue flaps with vascular pedicel, such as omentum, gracilis muscle, or rectal wall have been interposed between the rectum and urethra or vagina [2,3,8], but these procedures were too complex to perform. Moreover, the hypertrophied and dilated colon was difficult to be pulled through the rectum using a posterior sagittal incision alone, such as case 1 and case 4.…”
Section: Discussionmentioning
confidence: 99%
“…Several kinds of approaches such as transanal approach, anterior perineal transanorectal approach and transanal endorectal pull-through, and vascularized tissue flap interposition have been described [1][2][3], but clinical data showed that recurrence of the fistula is always accompanied with anal stricture and severe scars around the fistula, the mobilization and repair of fistula may be extremely difficult through the above methods [4].…”
Section: Discussionmentioning
confidence: 99%
“…1 Conservative treatment consisting of urinary diversion, broad-spectrum antibiotics, and parenteral nutrition is often initially attempted. Success rates as high as 25-50% have been reported, [1][2][3] however, conservative treatments often fail. If the fistula remains open after 3-6 months, further healing is unlikely with continued conservative management, so further treatment for fistula closure is needed.…”
Section: Discussionmentioning
confidence: 97%
“…A transanal or transperineal approach was used and all healed following 1 repair. Various surgical options are available to treat rectourethral fistula including transanal endorectal flap with or without biologic mesh reinforcement and transperineal repairs with the dartos or the gracilis interposition flap [3,8,[12][13][14][15][16][17][18][19][20][21][22]. Recently, advancement flap through a transanal endorectal microsurgery and closure after application of biologic glue have been described [23,24].…”
Section: Discussionmentioning
confidence: 99%